God and blackness : race, gender, and identity in a middle class Afrocentric church - Abrams, Andrea C. (NYU Press, 2014)
Offers an ethnographic study of blackness as it is understood within a specific community--the First Afrikan Presbyterian Church, a middle class Afrocentric congregation located in a suburb of Atlanta, Georgia. Drawing on nearly two years of participant observation and in-depth interviews, the author examines how this community has employed Afrocentrism and black theology as a means of negotiation the unreconciled natures of thoughts and ideals that are part of being both black and American.